Towards a Typology of Lexical Semantic Derivation Models: Linguistic and Psycholinguistic Aspects - Олег Деменчук (Психолінгвістика, 2020)
Objective. The paper focuses on lexical semantic derivation models and the ways they are explicated in experiential vocabulary. The study substantiates linguistic and psycholinguistic features of the models in the contrastive aspect (based on the Ukrainian and Polish languages).